2019
DOI: 10.1002/mrm.28135
|View full text |Cite
|
Sign up to set email alerts
|

Performance of compressed sensing for fluorine‐19 magnetic resonance imaging at low signal‐to‐noise ratio conditions

Abstract: Purpose:To examine the performance of compressed sensing (CS) in reconstructing low signal-to-noise ratio (SNR) 19 F MR signals that are close to the detection threshold and originate from small signal sources with no a priori known location. Methods: Regularization strength was adjusted automatically based on noise level.As performance metrics, root-mean-square deviations, true positive rates (TPRs), and false discovery rates were computed. CS and conventional reconstructions were compared at equal measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Multiple publications have demonstrated that the increased averaging enabled by CS can lead to sensitivity improvements for low SNR MRI [86,115,116]. The distribution of siponimod is less sparse than that of inflammatory lesions [86]. At the spatial resolution achieved in this study, the signal distribution has important features at the scale of single voxels, and thus does not possess the sparsity necessary for successful application of conventional CS techniques.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Multiple publications have demonstrated that the increased averaging enabled by CS can lead to sensitivity improvements for low SNR MRI [86,115,116]. The distribution of siponimod is less sparse than that of inflammatory lesions [86]. At the spatial resolution achieved in this study, the signal distribution has important features at the scale of single voxels, and thus does not possess the sparsity necessary for successful application of conventional CS techniques.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly shortened relaxation times were observed in ex vivo tissue, and we expect that the properties in in vivo tissues will not differ substantially. The effect of protein binding on the transverse relaxation times (reduction by up to 98%) creates challenges for pulse sequences which are employed in the more common 19 F MR methods such as point resolved spectroscopy (PRESS) or highly accelerated RARE in the case of perfluorocarbon imaging [37,[84][85][86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies were proposed to enhance 19 F‐MRI sensitivity including the use of high‐end cryogenic rf coils, [20] paramagnetic relaxation enhancement, [21] crystallographic defect induction, [22] compressed‐sensing‐based schemes [23] and even hyperpolarization techniques [24] . The 19 F‐GEST approach shown here offers an alternative strategy to detect very low levels of thermally polarized pools of fluorine‐19 spins with readily available hardware and can open new avenues for the development of advanced molecular architectures for the growing field of hotspot 19 F‐MRI, which, so far, has not been used for mapping targets at very low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…2d). The shown example is based on a dataset with fluorine nanoparticle labeled immune cells showing the sites of inflammation in a mouse model of multiple sclerosis (see Setup 4 in Starke et al [12] for details). The data preparation protocol is equally applicable to low SNR 19 F MRI of the kidney.…”
Section: Introductionmentioning
confidence: 99%